Population Structure, Genetic Diversity, and Evolutionary History of Kleinia neriifolia (Asteraceae) on the Canary Islands - Sun, Ye; Vargas-Mendoza, Carlos F. (Frontiers in Plant Science, 2017)
Kleinia neriifolia Haw. is an endemic species on the Canaian archipelago, this species is widespread in the coastal thicket of all the Canaian islands. In the present study, genetic diversity and population structure of K. neriifolia were investigated using chloroplast gene sequences and nuclear SSR (simple sequence repeat). The differentiation among island populations, the historical demography, and the underlying evolutionary scenarios of this species are further tested based on the genetic data. Chloroplast diversity reveals a strong genetic divergence between eastern islands (Gran Canaria, Fuerteventura, and Lanzarote) and western islands (EI Hierro, La Palma, La Gomera, Tenerife), this west-east genetic divergence may reflect a very beginning of speciation. The evolutionary scenario with highest posterior probabilities suggests Gran Canaria as oldest population with a westward colonization path to Tenerife, La Gomera, La Palma and EI Hierro, and eastward dispersal path to Lanzarote through Fuerteventura. In the western islands, there is a slight decrease in the effective population size towards areas of recent colonization. However, in the eastern islands, the effective population size increase in Lanzarote relative to Gran Canaria and Fuerteventura. These results further our understanding of the evolution of widespread endemic plants within Canarian archipelago.